INTRAOVA~IAN STUDIES AND FECUNDITY IN NEMIPTERDS JAPONICDS (BLOCH) - Dan, S S (Indian Journal of Fisheries, 2011)
Fecundity i,n Nemipterus japolliclIs (Bloch) va:n~ed from to.5 to 80.8 thousize.Among the four equa,(,jonJ, tested, the linear relationship be,tween ~ength andsands in fish ranging ,in size from 13.0 rtJo 20.9 em. and incre,ased with increasingfecundi,ty was closer tha.n the -rest. It was also found tha.t t'he fish bred twice ayea'r, once in De,cembe,r-Fehrua,ry and then in June-Ju:Jy. The spawning was shortand sha'rp.